Clinical features of Kawasaki disease initially mimicking retropharyngeal abscess: a retrospective analysis - Yong-chao Chen; Hong-guang Pan; De-sheng Jia; Hao-cheng Wang; Lan Li; Yi-shu Teng (BMC, 2022)
Abstract Objective Incomplete Kawasaki disease (IKD) initially presenting as retropharyngeal abnormality is very rare and is prone to misdiagnosis and missed diagnosis, often leading to poor prognosis. Most patients were misdiagnosed with retropharyngeal abscesses. Here, we describe and compare IKD patients initially presenting with retropharyngeal abnormalities, typical KD patients without retropharyngeal abnormalities and retropharyngeal abscess patients. Methods We performed a retrospective case-control study comparing IKD patients initially presenting with retropharyngeal abnormalities to both KD patients without retropharyngeal abnormalities and retropharyngeal abscess patients admitted to Shenzhen Children's Hospital between January 2016 and December 2021. Results We evaluated data from 10 IKD patients initially presenting with retropharyngeal abnormalities (Group A), 20 typical KD patients (Group B) and 16 surgical drainage confirmed retropharyngeal abscess patients (Group C). Compared to Group B, we observed that Group A was older and had a more intense inflammatory response. On the day of admission, Groups A and C had similar early clinical presentations, and there were no significant differences in any major signs or symptoms. Close observation for the development of new KD signs and symptoms and unresponsiveness to empirical antibiotic therapy after 3 days is extremely important. The CRP (p = 0.011), AST (p = 0.002) and ALT (p = 0.013) levels were significantly higher and the WBC (P = 0.040) levels were significantly lower in Group A than in Group C. Neck radiological findings, such as the presence of ring enhancement (p = 0.001) and mass effects on the airway, are also useful tools for distinguishing these two diseases. Conclusion The careful observation of the signs and symptoms of this disease and the comprehensive analysis of the laboratory tests and neck radiological findings may help clinicians become aware of retropharyngeal abnormality as an atypical presentation of KD. Then, unnecessary treatments could be reduced, and the occurrence of serious complications can be avoided.